Personal income in Malaysia: Distribution and differentials - Goh, Kim Leng; Tey, Nai Peng (Economics Bulletin, 2018)
Many studies on income disparities in Malaysia tend to use household data, focus on mean income, and ignore the distribution of income. The linkage to some of the characteristics of the individuals has not been examined. Using nationally representative data at the individual level, this paper shows empirically that the impact of demographic and socio-economic variables on income varies according to different income quantiles. The results of quantile regression suggest that education has a u-shaped effect on income among the graduates. Age and some occupational categories have stronger effects on income differentials at the top end of income distribution. On the other hand, the differentials attributed to gender, ethnicity and employment sector tend to decline as income level rises.